Factor analysis of educational evaluation indicators of Iranian sports coaches - Kiomars Aziz Malayeri (Revista Tempos e Espaços em Educação, 2021)
The objective of this study was factor analysis of educational evaluation indicators of sports coaches in Hamadan province. The statistical population of the study was all sports coaches in all sports branches in Hamadan province in the years (2019-2018). The statistical population of this study included all sports coaches in Hamadan province according to the latest information provided by the Statistics Center of the General Directorate of Sports and Youth in 2018, it included 4,000 people. The sampling method was stratified random; the number of samples was 351 based on Morgan table. The data collection tool was a researcher-made questionnaire that interviewed 30 experienced sports coaches and using Delphi technique and after agreeing on the materials, the results of the study were extracted and classified. Its nominal and content validity were reviewed and confirmed by a group of experts. The reliability of the instrument was calculated by Cronbach's alpha method of 0.85. Data were analyzed using heuristic rotation heuristic analysis, repeated measures analysis of variance and Bonferroni post hoc test at a significance level of P <0.050. Based on the results of factor analysis, out of 75 items of performance evaluation, 17 items were removed and 58 items were included in 6 factors. Social factors (5 items), professional (8 items), personality (8 items), managerial (14 items), scientific (14 items), emotional skills (9 items) in order of prioritizing the scientific factor in the first place, management in Second place, personality in third place, professional in fourth place, emotional in fifth place and social in sixth place. It is concluded that; Sports coaches in Hamadan province in all sports need scientific and managerial training according to the training of personality traits and these three priorities are considered by the trainers for training, respectively.